My body to you - Searle, Elizabeth, 1962- (Iowa short fiction award., 1993)
In the thirteen stories of My Body to You, thirteen women or girls pilot their own bodies through a shifting universe of lovers old and young, parents devoted and destructive, sisters of different sexes, children and adults living in the mysterious world of autism. All these characters share keen powers of observations and a heightened sensuality. In a wild variety of settings, they struggle to control--or dare to abandon themselves to--their intensely private passions.